Formation Motivational Mechanism of Labor Management for the Modern Enterprises - Kozinets, A. (Економічний вісник Донбасу, 2014)
In the article the view of staff motivation enterprises, allowing to assess the characteristics of the formation of new social values and motivational orientations knowledge economy that modify the behavior of modern people. The role of work motivation in providing enterprise development. The essence of the major theoretical approaches to the motivation of employees and their ability. Defined motives leading professional work opportunities for understanding the application of basic motivational theories to increase innovation activity staff. Formed generalized motivational mechanism for the modern enterprise. It was found that the existing mechanism of motivation into account such important motives of professional work, the motives of self, material and moral incentives, they fully contribute to the activities of employees. The main ways to improve the process of formation of motivation system, including the need for continuous monitoring measures to meet the needs of employees, evaluate existing tools from the standpoint of the formation, expansion methods of teaching staff.